National Ambulatory Medical Care Survey, 1980: Drug Mentions ([Verlag nicht ermittelbar], 1989)
This data collection is the latest in a series of surveys that offer information on patients' visits to a national sample of office-based physicians. The National Ambulatory Medical Care Surveys (NAMCS) collect information on all drugs/medications ordered, administered, or provided during the visits. In 1980 51,372 drugs were mentioned in the national sample of 46,081 patient visits. The data items include the medication code, generic name and code, brand name, entry status, prescription status, federal controlled substance status, composition status, and related ingredient codes.